A Hydrometallurgical Scheme for New Zealand Sulphide Ores - Kelly E. G (The Australasian Institute of Mining and Metallurgy, 1980)
New Zealand suffers the disadvantage of widely scattered ore bodies, none of which is large enough to economically support its own smelter. This leads to the concept of a centrally located smelter which must be flexible enough to cope with var